Investigation of Stroop Effect Using Event Related Potentials of Elite Karate Players - (:unkn) unknown (IEEE, 2015)
The Stroop Colour Word Test is a measurement technique to assess the cognitive flexibility and attention. Event related potentials via electroencephalography is used to examine the cortical activity differences during The Stroop Test. The aim of this study was to examine the electroencephalogram (EEG) activity during Stroop Test of elite Karate players (n=10) and control group (n=10). It was asked to participants to click on Right Arrow Key of the keyboard when the colour and the word was congruent and click on Left Arrow Key when it was incongruent. Event related potentials were recorded by EEG to analyse the performance of Stroop Test. There was no significant differences between Elite Karate players and control group during 390-410 ms comparing colour word match (p=0.36, p=0.24). There was a significant difference for all participant comparing to compatible answers.
Keywords: Karate; Cortical Activation; The Stroop Test; EEG; TASK; PERFORMANCE; INTERFERENCE; ERP